METODE PENDIDIKAN BERMAIN PERAN DALAM PEMBELAJARAN MORAL DAN KARAKTER DI SEKOLAH DASAR - Al Ghifari; Ayuni Putri N; Nisrina Febria E; Suwaibatul Aslamiyah; Yurika Gustiani R (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2024)
Educational methods in their function are very meaningful when learning takes place, especially in Moral and Character Learning in Elementary Schools. Learning can be conveyed well with one factor, namely appropriate educational methods. The Role Playing educational method is one of the various methods that can be used in the Moral and Character learning process. This research aims to analyze and identify related educational methods of Role Playing in Moral and Character learning in elementary schools. The implementation of this research was based on a descriptive qualitative approach with descriptive analysis data from various journal sources and researcher experience. The results of the research obtained examples of the application of the Role Playing educational method in Moral and Character learning in elementary schools, namely playing various kinds of characters such as Good, Evil and Cunning characters. Apart from that, in learning Character and Morals by exploiting problems of human relations by acting them out and it is understood that the Role Playing educational method consists of understanding the character of another individual and the form of responding to that character.